1997
DOI: 10.1364/oe.1.000441
|View full text |Cite
|
Sign up to set email alerts
|

Diffuse backscattering Mueller matricesof highly scattering media

Abstract: We report on the development of a method that records spatially dependent intensity patterns of polarized light that is diffusely backscattered from highly scattering media. It is demonstrated that these intensity patterns can be used to differentiate turbid media, such as polystyrene-sphere and biological-cell suspensions. Our technique employs polarized light from a He-Ne laser (l=543nm), which is focused onto the surface of the scattering medium. A surface area of approximately 4x4 cm centered on the light … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
95
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 163 publications
(104 citation statements)
references
References 17 publications
5
95
0
Order By: Relevance
“…A volume concentration of 0.12% was used in the study with calculated scattering coefficient of 41cm -1 and anisotropy (the g-parameter) of 0.93. The Mueller matrix images obtained in the polystyrene solution are similar as those reported before [20][21][22][23]. The M11 component of the Mueller matrix represents the unpolarized measurements.…”
Section: Resultssupporting
confidence: 79%
“…A volume concentration of 0.12% was used in the study with calculated scattering coefficient of 41cm -1 and anisotropy (the g-parameter) of 0.93. The Mueller matrix images obtained in the polystyrene solution are similar as those reported before [20][21][22][23]. The M11 component of the Mueller matrix represents the unpolarized measurements.…”
Section: Resultssupporting
confidence: 79%
“…Thus, the linear interpolation between two elements M 1 and M 2 of Mueller matrix space, is the straight line between both the points. Assuming normalized weights (sum of the weights equals 1), interpolation is a weighted mean following the relation: (6) It is worth noticing that computing first the interpolation curve on the HPD(4) matrix space, is also possible:…”
Section: Euclidean Distancementioning
confidence: 99%
“…The development of optical devices and systems [1], calibration procedures [2] and measurement inversion methods [3] [4] produced Mueller imaging systems with low noise measurement where the physical constraints on Mueller matrices are taken into account. These works contributed to popularize this imaging approach and examples of Mueller matrix imaging can be found for characterizing biological objects [5] or scattering media [6], with applications in dermatology [7], ophthalmology [8] or physics [9][10] for instance.…”
Section: -Introductionmentioning
confidence: 99%
“…The configuration of polarizer-compensator-analyzer (PCA) has been used for Müeller matrix determination with null ellipsometry from scattering media [21]. The two polarizers scheme was improved recently [22], to determine the Müeller matrix elements. It was shown that 49 intensity measurements with various orientations of polarizer and analyzer allow the determination of the 16 elements of the Müeller matrix of scattering media.…”
Section: Lc Devices With Applications For Polarimetric Imagingmentioning
confidence: 99%